Low‐Cost Dopant‐Free Carbazole Enamine Hole‐Transporting Materials for Thermally Stable Perovskite Solar Cells. Issue 1 (11th December 2021) - Zhou, Suer; Daskeviciene, Maryte; Steponaitis, Matas; Bubniene, Giedre; Jankauskas, Vygintas; Schutt, Kelly; Holzhey, Philippe; Marshall, Ashley R.; Caprioglio, Pietro; Christoforo, Grey; Ball, James M.; Malinauskas, Tadas; et al.
Abstract : Perovskite solar cells deliver high efficiencies, but are often made from high‐cost bespoke chemicals, such as the archetypical hole‐conductor, 2, 2′, 7, 7′‐tetrakis( N, N ‐di‐ p ‐methoxy‐phenylamine)‐9‐9′‐spirobifluorene (spiro‐OMeTAD). Herein, new charge‐transporting carbazole‐based enamine molecules are reported. The new hole conductors do not require chemical oxidation to reach high power conversion efficiencies (PCEs) when employed in n ‐type‐intrinsic‐ p ‐type perovskite solar cells; thus, reducing the risk of moisture degrading the perovskite layer through the hydrophilicity of oxidizing additives that are typically used with conventional hole conductors. Devices made with these new undoped carbazole‐based enamines achieve comparable PCEs to those employing doped spiro‐OMeTAD, and greatly enhanced stability under 85 °C thermal aging; maintaining 83% of their peak efficiency after 1000 h, compared with spiro‐OMeTAD‐based devices that degrade to 26% of the peak PCE within 24 h. Furthermore, the carbazole‐based enamines can be synthesized without the use of organometallic catalysts and complicated purification techniques, lowering the material cost by one order of magnitude compared with spiro‐OMeTAD. As a result, we calculate that the overall manufacturing costs of future photovoltaic (PV) modules are reduced, making the levelized cost of electricity competitive with silicon PV modules. Abstract : Perovskite solar cells deliver high efficiencies, but are often made from high‐cost bespoke chemicals, such as the archetypical hole‐conductor, 2, 2′, 7, 7′‐tetrakis( N, N ‐di‐ p ‐methoxy‐phenylamine)‐9‐9′‐spirobifluorene, spiro‐OMeTAD. In this work, new charge‐transporting carbazole‐based enamine molecules are reported.